Increasing Eleventh Graders’ Collaborative Skill in English Learning Through the Jigsaw Model at SMK Negeri 2 Gunungsitoli - Yarlin Nurlina Telaumbanua; Yaredi Waruwu; Riswan Zega; Afore Tahir Harefa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to increase the collaboration skill of 11th grade students in English learning through the application of the Jigsaw model at SMK Negeri 2 Gunungsitoli. The main problem identified was the low level of students' collaboration skills despite the use of group discussion methods, which were characterized by passive attitudes, lack of active contribution, ineffective communication, minimal mutual respect among group members, and suboptimal role distribution in group discussions. This study used the Classroom Action Research (CAR) method conducted in two cycles, each consisting of two meetings with planning, implementation, observation, and reflection stages. Data were collected through observation sheets, interviews, and documentation, then analysed qualitatively and quantitatively. The results showed a significant improvement in students' collaboration skills after the implementation of the Jigsaw model. In Cycle I, students' collaboration skills were rated as adequate with an average score of 64, while in Cycle II, they improved to outstanding with an average score of 86. This 22-point increase indicated the effectiveness of the Jigsaw model in facilitating active participation, communication, responsibility, and mutual respect within the group. In addition, the interview findings revealed several factors that hindered collaboration, such as lack of confidence, lack of time discipline, fear of rejection, and an unfavorable group atmosphere. This study implied that the Jigsaw model had proven effective in overcoming these barriers by clearly dividing tasks, forming expert groups for in-depth material exploration, and fostering individual and collective accountability. Thus, the implementation of the Jigsaw model could be an effective strategy to enhance students' collaboration skills in English language learning at vocational high schools, ultimately supporting the achievement of better learning outcomes.